2022
DOI: 10.1177/15269248221089013
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention Trial for Strengthening Medical Adherence after Heart Transplantation

Abstract: Introduction In heart transplant recipients, nonadherence is associated with higher risk of morbidity and mortality. Research Question Can a psychoeducational intervention enhance adherence to medical recommendations? Design We randomized 200 patients awaiting heart transplantation on the high urgency wait list to a manualized psychoeducational intervention or standard care. Follow-up continued to three years after transplantation. Primary endpoint was adherence to immunosuppressive medication, assessed at 3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…The “journey to the heart” script helps patients reframe their worry to a sense of caregiving. In trance, patients are invited to make gentle contact with their heart in a quiet space, listening with growing self-confidence to what it might wish to say and perhaps taking the opportunity to respond ( Tigges-Limmer and Schmid-Ott, 2012 ).…”
Section: Psychosocial Care Needs Of Heart Surgery Patients and Interv...mentioning
confidence: 99%
“…The “journey to the heart” script helps patients reframe their worry to a sense of caregiving. In trance, patients are invited to make gentle contact with their heart in a quiet space, listening with growing self-confidence to what it might wish to say and perhaps taking the opportunity to respond ( Tigges-Limmer and Schmid-Ott, 2012 ).…”
Section: Psychosocial Care Needs Of Heart Surgery Patients and Interv...mentioning
confidence: 99%
“…Auch nach der Transplantation werden Schulungen in standardisierter Form angeboten, die das Leben mit dem kürzlich transplantierten Organ im Fokus haben. Die Vermittlung erfolgt nach dem eigens entwickelten interdisziplinären Schulungsprogramm „Specific Active Refinement of Adherence of Heart Transplant Patients (SARAH)“ 24 28 . Dazu gehören unter anderem verschriftlichte Informationen für die häusliche Umgebung sowie praxisnahe Hinweise und Beratungen etwa über angemessene Ernährung, hygienische Verhaltensweisen oder das Management der medikamentösen Versorgung.…”
Section: Transplantationspflege In Der Stabilisierungsphaseunclassified
“…Von höchster Bedeutung sind insbesondere die Ablaufsteuerung durch die HTX-Koordination sowie die umfassende Betreuung durch das psychologische Team 16 28 . Neben dem ärztlichen und therapeutischen Dienst braucht es vor allem auch bei den Pflegenden 29 grundsätzlich ein hohes Maß an Spezialisierung und insbesondere einer strukturierten Einarbeitung 30 .…”
Section: Ausblickunclassified
“…There is research on transplantation-associated psychological factors of organ donors (see e.g., [2][3][4][5][6]) and on psychological factors associated with the procedure on the organ recipients' side as well (see e.g., [7][8][9][10]). Studies show that, in terms of psychological distress, the most frequently reported symptoms among organ recipients are anxiety symptoms (particularly fear of organ rejection, repeated surgery, and death) and symptoms of depression [11][12][13]. In addition, up to 16% of individuals show post-traumatic stress disorder (PTSD) following transplantation with symptoms such as scenic re-experiencing of events, emotional overload, nightmares, high internal tension, withdrawal, and avoidance behavior [14,15].…”
Section: Introductionmentioning
confidence: 99%